2010
DOI: 10.1159/000318808
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Participation in Providing Buccal Cell DNA for a Genetic Epidemiologic Study

Abstract: Aims: Our aim was to investigate factors associated with participation in buccal cell DNA collection using a large-scale prospective cohort study. Methods: Of the 183,634 Korea Medical Insurance Corporation (KMIC) prospective cohort study enrollees, 44,773 (36,794 men) were randomly selected. Buccal cell collection kits were mailed and collected from March to September 2004. Epidemiologic characteristics measured at baseline (1990 or 1992) and during follow-up (1998) were compared between respondents and nonre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
2
1
Order By: Relevance
“…These findings are consistent with another study which found that subjects with favorable lifestyle factors such as regular exercise, nonsmokers, and nondrinkers were more likely to participate in buccal cell collection. 8 We did find, however, that overall and in Hispanic mothers, those who consumed alcohol were more likely to participate in buccal cell collection. It is hypothesized that consumption of alcohol could be an indicator of higher socioeconomic status.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…These findings are consistent with another study which found that subjects with favorable lifestyle factors such as regular exercise, nonsmokers, and nondrinkers were more likely to participate in buccal cell collection. 8 We did find, however, that overall and in Hispanic mothers, those who consumed alcohol were more likely to participate in buccal cell collection. It is hypothesized that consumption of alcohol could be an indicator of higher socioeconomic status.…”
Section: Discussioncontrasting
confidence: 60%
“…Furthermore, the potential biases that arise as a result of low participation rates can also be better evaluated. 4 The few previous studies that have investigated differences between participants who provided biological samples and those who declined to do so 6,8,13,14 demonstrated that race/ethnicity, age, health status, education, and other demographic factors are associated with participation. 8,9,1417 A previous analysis of buccal cell participation at 1 of 10 study sites of the National Birth Defects Prevention Study (NBDPS) found that non-Hispanic white race, higher maternal education, and the addition of monetary incentives were associated with higher participation in buccal cell collection.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies did not assess sociodemographic differences between responders and non-responders (Cozier et al, 2004; Etter and Bullen, 2011; Egan et al, 2003; Feigelson et al, 2001; Freeman et al, 1997; Hansen et al, 2007). Several of the studies that did assess differences found significant response variation by sociodemographic factors such as age (Avendano et al, 2011; Bloomfield et al, 2003; Boyle et al, 2010; Etter and Perneger, 2001; Kang et al, 2011; Kozlowski et al, 2002; Margolis et al 2011; Rylander-Rudqvist et al, 2006) and race (Bloomfield et al, 2003; Boyle et al, 2010; Crider et al, 2006; Kozlowski et al, 2002; Le Marchand et al, 2001). Others, however, found no statistically significant differences in compliance by these factors (Bauer et al, 2004; Etter et al, 2005; Fidler et al 2011; Halpern et al, 2012; Osmond et al, 2000).…”
Section: The Track Record For Low Cost Biomeasurmentmentioning
confidence: 99%